Resource Distribution and Benefit Sharing in Baghmara Buffer Zone Community Forest: Implications for Sustainable Livelihoods in Nepal (The Lumbini Journal of Business and Economics, 2026)
Purpose: The study examines the distribution pattern and benefit sharing of forest resources at the Baghmara Buffer Zone Community Forest (BBZCF) in Chitwan, Nepal, with focus on how community forestry (CF) supports local livelihoods.Methods: Structured questionnaires were used to collect data from 71 households in the study area. Descriptive statistics including Lorenz curve and Gini coefficient were employed to analyze the collected data and the results are presented in tables and figures.Results: Low-value products are mainly accessed by marginalized groups, whereas high-value timber is largely captured by elite groups. The comparative analysis of the Lorenz curve shows that although there is an equitable distribution of subsistence resources among caste/ethnicities (Gini=0.051) and wealth rank (Gini=0.119), high-value timber exhibits substantial inequality, which is more concentrated among dominant wealth rank (Gini=0.549) than caste/ethnicity groups (Gini=0.268).Conclusion: The study of BBZCF shows that CF supports sustainable livelihoods of local people but there are found persistent inequalities in high-value resources like timbers. Enhancing inclusiveness in forest resource distribution can improve outcomes of local livelihoods and reduce socio-economic inequalities.